Post COVID-19 persistent fatigue: a proposal for rehabilitative interventions in the spa setting - Maccarone, Maria Chiara; Magro, Giacomo; Tognolo, Lucrezia; Masiero, Stefano (International journal of biometeorology, 2021)
With this letter to Editor, we aim at offering our viewpoint on the potential use of the spa resources to contribute to the treatment of persistent COVID-19 sequelae. In particular, our argumentations focus on the comprehensive management of fatigue persisting after the resolution of the acute infection. This sequela seems to be the most frequent disabling outcome, leading to a delay in social reintegration and return to working life. We suggest that spa facilities including multidisciplinary interventions and trained staffs could be an appropriate setting for providing rehabilitative protocols to treat chronic fatigue in post COVID-19 subjects. Spa treatments may improve the physical symptoms of chronic fatigue and modulate the immune imbalance, reducing persisting inflammation. Moreover, in the spa setting, specific respiratory rehabilitation and neuropsychological interventions could be provided. The rehabilitative protocol could also properly address comorbidities. In conclusion, respecting the hygiene and preventive measures, the spa setting could represent the appropriate environment to take care of post-COVID chronic fatigue, offering adequate and multidisciplinary rehabilitation protocols. Further, prospective trials on this topic are needed to fully evaluate the positive impact of a comprehensive rehabilitative treatment in the spa environment for subjects with post-COVID-19 fatigue.